International Retailers' Performance in Host Countries The Roles of Strategies, Consumer Perceptions and the Local Environment - Morbe, Lukas (Handel und Internationales Marketing Retailing and International Marketing,, 2018)
Lukas Morbe sheds light on important antecedents of international retailers' local performance including international strategies and their local implementation, local consumers' perceptions as well as the wider country- and format-specific environment. This topic is of exceptional relevance due to the specific challenges that retail companies face with their increasing internationalization. Retailers transfer their formats across the globe while their business is local in nature and requires attention to the performance in each individual host country. The results of the presented analyses aim to inform retail managers' decisions in international expansion and operation, but also allow for theoretical implications for future research in the fields of retail management and international business. Contents International Strategy's Effects on Retailers' Local Implementation and Performance An Inter- and Intra-format Perspective on Transfer and Perception of Retail Formats Country Environment, Retailers' Resources and Local Performance: A Cross-Classified Multi-level Approach Target Groups Researchers and students of business administration with majors in international management in general and retail management or retailers' internationalization in particular Executives, managers, and experts in the fields of management and international expansion of retail firms About the Author Dr. Lukas Morbe worked as research assistant at the Chair for Marketing and Retailing at Trier University, where he received his doctoral degree.